Annual Plan Format 1980-81 and Mid-Term Fifth-Year Plan 1978-83 Government of Himachal Pradesh - Planning Commission (Planning Commission, 1980)
The Fifth Five Year Plan( 1974-79) for Himachal Pradesh was finalised at Rs. 235.95 crores at the N.D.C. meeting held in September,1976. Due to mounting inflationary pressures as a result of spiraling prices, the release of plan outlays for Himachal Pradesh remained at a low key during 1974-77 period. Some leeway was made up during the 1977-78 plan when our plan size recorded a step up of about 50 percent over the 1976-77 level.
Government of Himachal Pradesh, Planning Commission